Bem-estar social nos anos e 2000: Traços estilizados da história brasileira - André Gambier Campos (Instituto de Pesquisa Econômica Aplicada (IPEA), 2015)
– In a stylized way, this text presents the dynamics of the welfare in Brazil in recent decades, highlighting especially the 2000's. Firstly, the purpose is to check some basic indicators of well-being (or of lack of it), as those related to poverty and extreme poverty situations. Secondly, the objective is to analyze some factors responsible for this welfare, as those associated with the household income, which comes from the labor market and from the social policy.
Keywords: J00; I00; I30; 330; labor; social policy; welfare